LEARNING ORGANIZATION AS DRIVERS OF HUMAN RESOURCES 4.0 AT THE TECHNICAL UNIVERSITY OF MALAYSIA MELAKA (UTEM) - Norliah, Kudus; Muliati, Sedek; Mahadi, Abu Hassan; Z., Ab Rahman (Journal of Human Capital Development (JHCD), 2023)
ABSTRACT The borderless and dynamic globalization environment has forced universities to operate in a more complex and competitive higher education landscape. Hence, it is important for universities to function as learning organizations to ensure their survival, be resilient and achieve sustainable growth especially in the era of Industry 4.0. This study, which used the case study method involving Malaysian public universities, intended to investigate the implementation of learning organization practices as main drivers. Data were collected by conducting interviews involving eight respondents from each university and were analysed qualitatively. The study sample comprised three categories of human resource personnel, namely executives, management staff and academic staff. Findings show that the universities had managed their three subsystems, namely leadership, work system and structure, as well as resilient performance and staff development, at different levels. Among the three subsystems, work system and structure were identified to be at the highest level, followed by leadership and finally, resilient performance and staff development. The seven learning organization practices which were information flow, organizational climate, individual/group development, individual/group practices, vision and mission staff achievement and feedback found to be main drivers among the human resources personnel. Conversely, five practices that were yet to become common learning organization practices were executive practices, work systems and organizations, training and education, management practices, as well as reward and recognition. Universities that function as learning organizations assume learning to be a catalyst for the development of resilient human resources. Therefore, the university is able to survive and sustain its dynamics in a competitive environment in a higher education system, especially in the era of Industry 4.0. This paper may have some direct implications towards the industrial 4.0 (IR4.0) movements in Human Resources in Malaysia which able to provide new insight into the exploration of the idea through the practice of learning organization. Keywords: learning organisation, human resources, industry 4.0, implementation, university